Implementing a digital system for contact tracing and case investigation during COVID-19 pandemic in San Francisco: a qualitative study. Issue 4 (29th October 2021) - Burgess, Hailey; Gutierrez-Mock, Luis; Ho, Yun-Xian; Moghadassi, Michelle; Lesh, Neal; Krueger, Elizabeth; Reid, Michael
Abstract: During the COVID-19 pandemic, many health jurisdictions deployed digital informatics systems to support "manual" case investigation and contact tracing (CICT). This case study evaluates the implementation and use of a digital information system through the experiences of CICT workers in the City and County of San Francisco (CCSF). We conducted semi-structured, 90-min interviews with a sample of the CCSF CICT workforce ( n = 37). Participants also completed standardized assessments of the digital system using the System Usability Scale (SUS). Qualitative analyses highlighted (1) the importance of digital tools to ensure rapid onboarding and effective data capture in a public health emergency; (2) the use of digital systems to support culturally sensitive care; and (3) the role of digitals tools in building supportive work environments. The mean SUS score was 70/100 (SD = 17), indicating relative ease of use. In summary, the analysis highlights the importance of digital tools to support manual CICT in the COVID-19 response. Lay Summary: During the COVID-19 pandemic, many health departments implemented digital systems to collect, store, and share data for case investigation and contact tracing (CICT). In San Francisco, much of the contact tracing workforce was entirely remote and had little to no public health experience. Given this unique situation, we wanted to understand their experience with the digital system to inform future implementation of digital systems for public health responses. This case study describes how CICT workers in San Francisco experienced and used the digital system and how it could be improved. We conducted semi-structured, 90-min interviews and a short survey with a sample of 37 CICT workers and found that, overall, the digital system was easy to learn and improved workers' experience of data management during the pandemic. The digital system was also important in fostering a supportive and collaborative work environment. We found that the system could be improved to better support culturally sensitive care and highlight the importance of digital systems in ensuring equitable public health responses.